Ethnobotanical survey of medicinal plants used for the treatment of diabetes in Manisa, Turkey - Durmuskahya, C.; Ozturk, M. (Universiti Kebangsaan Malaysia, 2013)
In this study, medicinal plants which are traditionally used for treatment of diabetes mellitus in Manisa and its environs have been investigated. A detailed market survey and ethnobotanical enquiry was performed in the region. In all, 121 medicinal herb dealers were interviewed together with the patients suffering from diabetes. After questionnaire studies, plant specimens were collected from medicinal herb markets known locally as ‘aktars’ or ‘baharatchi’, a total of 27 plant taxa belonging to 15 families were identified to be used for the treatment of diabetes. These taxa mostly belonged to the families Rosaceae (5 taxa), Lamiaceae (3 taxa), Fabaceae (2 taxa) and Asteraceae (2 taxa). The most important anti-diabetic plants are; Zizyphus jujube Mill. (jujube), Origanum onites L. (oregano), Ceracus mahaleb L. (mahaleb) and Trigonella foenum-graecum L. (fenugreek). Attempts are being made to investigate their active compounds responsible for the hypoglycemic activity.